Dialectical Unity in Central America? An Analysis of its Dialectical Lexicon - Cáceres-Lorenzo, María-Teresa (Onomázein, 2020)
The lexicon that coincides with the geographic region formed by the six countries of the American isthmus has not yet been examined as part of a single dialectical area. Our inquiry proposes to analyse and classify the lexical units that are recorded in dialectical dictionaries as a means to answer the question of whether this is a single dialectical area. Through a quantitative and qualitative methodology, we discover that the Central American territory presents two groups according to lexical repertoire. The results demonstrate that the first includes El Salvador, Guatemala, Honduras and Nicaragua, which have a greater number of coinciding words compared to Costa Rica and Panama. Data about the indicators that shed light on etymological origin and lexical-semantic creation, adoption and adaptation to understand the trends followed by each group are also provided. This work contributes to the possibility of considering Central America as a dialectical unit.